Biochemical and cytochemical studies of the enzymatic activity of the venom glands of workers of honey bee Apis mellifera L. (Hymenoptera, Apidae) - Magalhaes de Abreu, Rusleyd Maria; Morelli Silva de Moraes, Regina Lucia [UNESP]; Camargo-Mathias, Maria Izabel [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
Biochemical studies revealed that the activity of some hydrolytic enzymes from the venom glands of honey bee Apis mellifera was higher in workers of 14 days of age than in those of 40 days. Among these enzymes, the highest activity was recorded for acid phosphatase, which was cytochemically detected throughout the length of the secretory filament and surrounding the canaliculi of the distal region of the reservoir. The acid phosphatase was considered to be a typical secretion product, since it was present in the cytoplasm as well as in the canaliculi of the secretory cells. (c) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bees; Enzymatic activity; Venom gland